Procalcitonin Levels in Critically Ill Children With Status Asthmaticus. Issue 10 (October 2019) - Samraj, Ravi S.; Crotty, Eric J.; Wheeler, Derek S.
Abstract : Background: Children with status asthmaticus (SA) often present with fever and are evaluated with chest radiographs (CXRs). In the absence of a confirmatory test for bacterial infection, antibiotics are started whenever there are radiological infiltrates or if there is a suspicion of pneumonia. We undertook this study to determine if serum procalcitonin (PCT) levels at admission are altered in critically ill children with SA. We also sought to determine if serum PCT levels are elevated in children with radiological infiltrates or in children who were treated with antibiotics. Methods: This is a prospective single-center observational study evaluating serum PCT levels in critically ill children with SA. Study subjects included children 1 to 21 years old, admitted to a pediatric intensive care unit (PICU) with SA between March 2012 and April 2013. For the purposes of this study, patients whose CXRs were read by the radiologist as probable bacterial pneumonia was defined as having "radiological bacterial pneumonia, " whereas patients who received antibiotics by the treating physician were defined as having "clinician-diagnosed pneumonia." Results: Sixty-one patients with a median age of 7.3 years (interquartile range, 4–10 years) were included in the study. Fifty-one percent were male. Average Pediatric Risk of Mortality III score was 2.7 (SD, 2.9). Three patients (5%) were determined to have radiological bacterial pneumonia, whereas 52 (85%) did not. Six patients (10%) were indeterminate. The mean PCT level for all patients was 0.65 (SD, 1.54) ng/mL, whereas the median PCT level was 0.3 ng/mL. There was no significant difference in the mean PCT levels between the patients with and without clinician-diagnosed pneumonia (0.33 [SD, 0.36] vs 0.69 [SD, 1.67], P = 0.44). Using a PCT cutoff level of 0.5 ng/mL, a significant association was found with the presence of fever ( P = 0.004), but no significant association was found with the presence of CXR infiltrates, radiological bacterial pneumonia, hospital length of stay, PICU length of stay, Pediatric Risk of Mortality III scores, or receipt of antibiotics. Conclusions: Serum PCT level was not elevated to greater than 0.5 ng/mL in 75% of this cohort of critically ill children with SA admitted to PICU. Presence of CXR infiltrates was not associated with higher PCT levels. Large clinical trials are needed to study the diagnostic and predictive role of PCT in this patient population.